Agenesis of right lobe of liver; a rare anomaly: a case report - Nikam, Vasudha Ravindra; Kitture, Balkrishna Shankar (International Journal of Research in Medical Sciences, 2017)
Agenesis of right lobe of liver is a rare finding and was defined as the absence of liver tissue on the right side with preservation of the middle hepatic vein without previous disease or surgery. Congenital agenesis of right hepatic lobe is a rare anomaly which is found incidentally in radiologic examination. Here we present a case of 22 year old female who came with abdominal distension suspecting liver cirrhosis she was investigated and on imaging studies incidentally it was revealed that there is absence of right lobe of liver.